The Difference In The Effect Between Abdominal Breathing Techniques And Deep Back Massage On Reducing Labor Pain During The Active Phase I At Cengkareng Hospital In 2022 - Lili Farlikhatun; Ira Hanurawati (International Journal of Health and Pharmaceutical (IJHP), 2023)
Labor pain is the main problem experienced by maternity mothers (Rahayu, 2018). In Brazil, labor pain reaches more than 50% of the birth rate in a hospital which is the highest percentage worldwide (Alam, 2020). A preliminary study conducted by the authors, in May 2022, of 10 maternity mothers, 7 (70%) mothers felt severe pain, 2 (20%) mothers felt moderate pain, and 1 (10%) mothers felt mild pain. Therefore, the author is interested in conducting research on pain management with non-pharmacological methods in the form of relaxation and massage, on this occasion the author will conduct research on the difference between abdominal breathing techniques and deep back massage on reducing labor pain during the active phase I in physiological childbirth at Cengkareng Hospital in 2022. Knowing the difference in the influence between abdominal breathing techniques and deep back massage on reducing labor pain during the active phase at cengkareng hospital in 2022. This type of research is quantitative research, research design using quasi-experiments with one group pretest and posttest design. The sampling technique is a consecutive sampling technique, with a total sample of 44 respondents. Data processing using the T-test. Based on the results of independent analysis-test, a p value of 0.000 (p value < α 0.05) was obtained with a deep back massage standard deviation of 0.512 < 0.528 so that the results were obtained that H0 was rejected and Ha was accepted. From these results, it is concluded that there is a difference between abdominal breathing techniques and deep back massage in overcoming labor pain during the I active phase. Thus from both techniques more effective against pain adaptation response is deep back massage. The conclusion of this study is that deep back massage is more effective than abdominal breathing techniques with a standard deviation of 0.512 < 0.528 and a p value of 0.000 (p value < 0.05).